Assemblage, food justice, and intersectionality in rural Mississippi: the Oktibbeha Food Policy Council. Issue 6 (1st November 2020) - Thompson, Diego; Johnson, Kecia R.; Cistrunk, Kenya M.; Vancil-Leap, Ashley; Nyatta, Thomas; Hossfeld, Leslie; Rico Méndez, Gina; Jones, Claudette
Abstract: Oktibbeha County (Mississippi) is among the highest food cost and food insecure counties in the nation. In 2016, a group of scholars from a land-grant university held periodic meetings to address food insecurity, food access, and local food systems development, creating the Oktibbeha Food Policy Council (OFPC). A large body of literature on food justice, intersectionality, food policy councils, and agri-environmental assemblage highlights the importance of these types of collaborative initiatives to facilitate better availability and access to fresh and healthy food among historically marginalized groups. However, little has been studied on how food policy councils can be generated and evolve in historically marginalized rural communities of the South. By analyzing the OFPC, this paper aims to contribute to this gap in the existing literature, exploring what factors led to its creation and development. Results of this study show how food justice and the intersection of race and socioeconomic status with local agri-food problems influenced the assemblage and work of this group, creating new opportunities, for low-income families and limited resource Black farmers. Discussions and conclusions center on the lessons, opportunities, and challenges learned from this experience and critical aspects that may be contemplated by similar initiatives and contexts.